Pembelajaran Individual Berbasis Kekuatan sebagai Strategi Peningkatan Keterlibatan dan Kemandirian Anak Berkebutuhan Khusus - Framz Hardiansyah; Ananda Nurhabibah; Moh. Daufir Rahman; Fikri Ardiansyahputra; Ach. Zaim Musleh (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning for children with special needs requires instructional approaches that can accommodate the diversity of students’ characteristics, potentials, and learning needs. One relevant approach is strength-based individual learning, which is designed by building on students’ potentials and strengths. This study aimed to analyze the implementation of strength-based individual learning as a strategy to enhance the engagement and independence of children with special needs at SLB Negeri Sumenep. This research employed a qualitative approach using Classroom Action Research (CAR) conducted in two cycles. The research subjects consisted of three students with special needs who had different types of learning barriers. Data collection techniques included observation, interviews, and documentation, while data analysis was carried out qualitatively through data reduction, data display, and conclusion drawing. The results showed that the implementation of strength-based individual learning significantly increased students’ learning engagement, as indicated by improvements in attention, active participation, and emotional involvement during the learning process. In addition, students’ learning independence also improved, as evidenced by reduced dependence on teacher assistance and increased ability to complete tasks independently. These findings indicate that strength-based individual learning is an effective and applicable strategy for improving the quality of education for children with special needs in special schools.